Analysis of Croatian public museums’ digital initiatives amid COVID-19 and recommendations for museum management and governance - Edgar Buršić; Tea Golja; Hermina Maras Benassi (Management : Journal of Contemporary Management Issues, 2023)
The COVID-19 pandemic has presented challenges for public museums in Croatia. This study examines how museum management and professionals have responded to the closure of museums during the pandemic by exploring digital initiatives and online engagement with remote audiences. The authors analysed data from 162 Croatian museums registered in the Museum Documentation Centre in Zagreb to investigate the relationship between socioeconomic and demographic indicators and museums’ digital activities using multiple regression analysis. The findings revealed that half of the museums in the sample were active online, with social media being a commonly used platform. Interestingly, museums with a stronger online presence, lower regional unemployment rates, and a lower tourism development index were more likely to engage in activities during the pandemic. The authors conclude with recommendations for museum management and governance to embrace digital acceleration and adapt to the digital age. The study findings hold significant relevance for museums preparing for future pandemics or crises as they highlight the importance of digital initiatives and online presence in ensuring continued engagement with audiences during periods of closure. By leveraging digital tools and platforms, museums can overcome physical limitations and effectively reach remote audiences, thereby enhancing their resilience and adaptability in times of crisis. This study contributes to the understanding of museums’ digital transformation in response to the COVID-19 pandemic and provides valuable insights for museum practitioners, policy-makers, and researchers to shape future strategies. Further research could explore the long-term impacts of digital initiatives on museums’ sustainability and visitor engagement beyond the pandemic context.